THE EVOLUTION OF PAYMENT SYSTEMS ARCHITECTURE: ALIGNING WITH REGULATORY COMPLIANCE IN THE DIGITAL AGE - Chinnapa Reddy Yeruva (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2024)
This comprehensive article explores the transformation of payment systems architecture in response to evolving regulatory requirements and technological advancements. The article examines the transition from legacy systems to modern architecture, highlighting the challenges financial institutions face in maintaining compliance while innovating. It analyzes key regulatory drivers, including PSD2, Dodd-Frank, and AML requirements, and their impact on architectural decisions. The article delves into essential components of modern compliance systems, including microservices, event-driven architectures, and data privacy frameworks. Furthermore, it outlines future-proofing strategies and best practices for maintaining regulatory compliance in an increasingly complex financial ecosystem. The article demonstrates how financial institutions can effectively balance innovation with regulatory requirements through strategic architectural choices and robust compliance frameworks.